ORGANOLOGI INSTRUMEN GAMBANG DALAM KESENIAN GAMBANG KROMONG PRODUKSI TOTONG DI RAWA KUCING, TANGERANG - Setyatama, Agung; Rustandi Mulyana, Aton (Program Studi Pendidikan Musik, 2024)
This research discusses the study of gambang organology in the art of Gambang Kromong through the production of the Totong version of the gambang. Gambang is a Betawi traditional musical instrument in the form of a xylophone with a special wood called Merawan wood. This study aims to examine the organology of gambang based on observations, descriptions, and analysis of the aspects involved in it. The term organology comes from the ancient Greek